Psychometric Validation of the Flourishing Scale among LGBT Population - González-Rivera, Juan (2026)
Introduction: Flourishing is a key indicator of positive mental health and psychosocial functioning. However, evidence on the measurement performance of the Flourishing Scale (FS) in sexual and gender minority (LGBT/SGM) populations in the Spanish-speaking Caribbean remains limited. Objective: To evaluate the psychometric properties of the FS among LGBT adults in Puerto Rico. Method: Participants were recruited online (N = 300). Given item-level and multivariate non-normality, a robust one-factor CFA was estimated and examined global fit, standardized loadings, and reliability (α, ω). Evidence for validity included (a) Average Variance Extracted (AVE) as an indicator-level convergence index and (b) associations with external criteria (PHQ-8, GAD-7). Multi-group CFA tested configural, metric, and scalar invariance across gender identity and sexual orientation. Results: The robust CFA supported a unidimensional structure with strong standardized loadings and high internal consistency. AVE exceeded .50, indicating adequate indicator-level convergence within the measurement model. As hypothesized, FS scores correlated negatively with PHQ-8 and GAD-7. Multi-group CFA supported metric and scalar invariance by gender identity and scalar invariance by sexual orientation, with borderline evidence at the metric step, enabling latent-mean comparisons under supported conditions. Conclusions: The FS is a brief, reliable, and valid indicator of psychological flourishing among LGBT adults in Puerto Rico, suitable for research, screening, and program evaluation; however, convergent validity with an independent positive well-being measure should be established in future work.